Controlled Ice Nucleation Using Freeze-Dried Pseudomonas syringae Encapsulated in Alginate Beads - Weng, Lindong (Cryobiology, 2017)
The control of ice nucleation is of fundamental significance in many process technologies related to food and pharmaceutical science and cryobiology. Mechanical perturbation, electromagnetic fields and ice- nucleating agents (INAs) have been known to induce ice nucleation in a controlled manner. But these ice-nucleating methods may suffer from cumbersome manual operations, safety concerns of external fields, and biocompatibility and recovery issues of INA particles, especially when used in living systems. Given the automatic ice-seeding nature of INAs, a promising solution to overcome some of the above limitations is to engineer a biocomposite that accommodates the INA particles but minimizes their interactions with biologics, as well as enabling the recovery of used particles. In this study, freeze-dried Pseudomonas syringae, a model ice-nucleating agent, was encapsulated into microliter-sized alginate beads. We evaluated the performance of the bacterial hydrogel beads to initiate ice nucleation in water and aqueous glycerol solution by investigating factors including the size and number of the beads and the local concentration of INA particles. In the aqueous sample of a fixed volume, the total mass of the INA particles (m) was found to be the governing parameter that is solely responsible for determining the ice nucleation performance of the bacterial hydrogel beads. The freezing temperature has a strong positive linear correlation with log(10)m. The findings in this study provide an effective, predictable approach to control ice nucleation, which can improve the outcome and standardization of many ice- assisted process technologies.